Characteristics Of The Most Most ENT-Kl Diseases In Polyclinics: Literature Review - Amaliah Fildzah AH; Sri Wartati; Rahmawti Akib (Jurnal EduHealth, 2024)
Introduction:Ears, nose and throat (ENT) are vital body organs for humans. This is because ENT is related to the hearing and respiratory systems in humans. Most cases of ENT disease come from bacterial and viral infections. Objective:This literature aims to see the characteristics of the most common ENT diseases in the Polyclinic. Method: This study used a literature review method with the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) protocol. Scientific articles or journals were downloaded from PubMed, Garuda Portal, and Google Scholar with SINTA IV and V standards. The keywords in the search for this article were characteristics, ENT-KL disease in polyclinics, 244 articles were obtained in the search results. All articles were selected based on the inclusion criteria, resulting in 5 research articles that would be reviewed. Results: In this literature, there were 5 research articles that reported the characteristics of the most ENT diseases in polyclinics. Conclusion: The most common characteristics of ENT diseases in the polyclinic are cerumen obturans, otitis externa, rhinosinusitis and otitis media.